2012
DOI: 10.7863/jum.2012.31.11.1731
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Ultrasonographic Assessment of Fetal Total Lung Volume as a Prognostic Factor in Primary Pleural Effusion

Abstract: Fetal total lung volumes may be useful for the prediction of perinatal outcomes in primary pleural effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Only one report has shown that fetal total lung volume measured by three-dimensional ultrasound before birth was significantly associated with the survival of cases with primary FHT. 8 We showed a relationship between the lung size assessed by 2D ultrasound after TAS and the mortality of hydropic primary FHT.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Only one report has shown that fetal total lung volume measured by three-dimensional ultrasound before birth was significantly associated with the survival of cases with primary FHT. 8 We showed a relationship between the lung size assessed by 2D ultrasound after TAS and the mortality of hydropic primary FHT.…”
Section: Discussionmentioning
confidence: 72%
“…We hypothesize that the evaluation of the fetal lung size, which estimates the degree of pulmonary hypoplasia, may be useful for predicting the survival of fetuses with primary FHT. However, there have only been a few previous reports on the treatment of fetal lung size in primary FHT . In addition, absent or reversed end‐diastolic velocity (AREDV) in the umbilical artery (UA) is often found in hydropic fetuses with a poor prognosis and is used as one of the cardiovascular parameters of fetal hydrops .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is inappropriate to use the same spherical formula to assess the BPS sizes of all types. In our present study, we measured BPS volumes by using 3D ultrasound with VOCAL, as our previous study [3], which avoids assumptions about lesion shapes and assures the accuracy of volume measurements [21]. Collectively, our study provides a new strategy to predict the growth of BPS and the associated hydrops in order to offer suggestions regarding the clinical management.…”
Section: Discussionmentioning
confidence: 99%